2018
DOI: 10.1097/icl.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Concepts of the Etiology and Treatment of Myopia

Abstract: Abstract:Myopia occurs in more than 50% of the population in many industrialized countries and is expected to increase; complications associated with axial elongation from myopia are the sixth leading cause of blindness. Thus, understanding its etiology, epidemiology, and the results of various treatment regiments may modify current care and result in a reduction in morbidity from progressive myopia. This rapid increase cannot be explained by genetics alone. Current animal and human research demonstrates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
163
0
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 222 publications
(181 reference statements)
3
163
0
21
Order By: Relevance
“…Myopia is characterized by an increase in eye size and is accompanied by structural changes in the sclera, the outer coat of the globe that determines ocular shape. The currently available treatments for myopia include multifocal soft contact lenses, radial refractive gradient lenses, bifocal spectacles, or orthokeratology [7]. In terms of pharmaceutical interventions, atropine has recently received most attention [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Myopia is characterized by an increase in eye size and is accompanied by structural changes in the sclera, the outer coat of the globe that determines ocular shape. The currently available treatments for myopia include multifocal soft contact lenses, radial refractive gradient lenses, bifocal spectacles, or orthokeratology [7]. In terms of pharmaceutical interventions, atropine has recently received most attention [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Myopia is a worldwide visual impairment 1 . Myopia has increased from 25% to 44% between 1972 and 2004 in the United States 1 .…”
Section: Textmentioning
confidence: 99%
“…The radiated hole and the macular hole 1. The most common macular change in highly myopic eyes is macular holes [23][24][25][26][27][28] .…”
Section: Eye Elongationmentioning
confidence: 99%
“…Myopia is the most common visual disease worldwide. The prevalence of myopia in children in developed countries of East and Southeast Asia is estimated to be 80-90% [1]. Although our knowledge of the mechanisms that underlie the development and progression of myopia remains limited, studies in guinea pig models of myopia have shown that recovery from myopia can occur after the deprived eye is re-exposed to a normal environment [2].…”
Section: Introductionmentioning
confidence: 99%